Systematic Elements in the Linkage of National Stock Market Indices - Ripley, Duncan M. (The Review of Economics and Statistics, 1973)
PpT HE purpose of this paper is to investigate the systematic covariation between stock prices in developed countries. Covariation may reflect causation or it may indicate similar reactions to external stimuli. Causal relationships may be lasting or temporary and may accordingly result in sustained periods or in rather brief periods of covariation. For example, developments in the Canadian stock market are continuously influenced by those in the United States stock market. An example of the second type of causal covariation is the relationship between Japanese and United States stock prices in mid-1970. Because of a decline in United States stock prices at this time and the liquidity needs of large institutional investors in the United States, it was necessary for these investors to reduce their holdings of foreign assets.1 The reduction of their investment in Japanese equities resulted in an outflow of capital from Japan and stimulated a decline in Japanese equity prices. For markets outside the United States, the introduction of the Interest Equalization Tax by the United States in mid-1963 is an example of an external development that caused similar responses in several stock markets. This measure caused many stock indices to decline, especially those in Japan and Canada. To the extent that stock prices reflect domestic economic conditions and conditions are similar across countries, stock prices will show systematic covariation that is a result of developments external to the national stock markets. Covariation between stock prices in different countries is of interest to individual investors who wish to allocate their investment portfolios so as to maximize the rates of return on their portfolios for a given risk. The return on stock consists of the dividend paid on the stock and the change in the price of the stock. For most stocks the price is more variable than the dividend so that price movements account for a larger part of the change in the rate of return. Thus investors seeking effective portfolio diversification wish to determine the countries whose stock prices move together, those whose stock prices move in opposite directions, and those whose stock price movements are unrelated to one another. Covariation between stock prices in different countries is of interest to the forecaster and policy maker because stock movements affect domestic consumption and investment expenditures. The wealth of consumers is affected by changes in stock prices and changes in wealth affect consumption decisions. The mechanism through which stock price changes affect investment decisions is more complex, but the influence of these changes may still be significant. An economist is frequently interested in establishing the extent to which financial markets are integrated or the extent to which developments in one market are reflected in the developments in a second market. Measures of financial integration are traditionally based on the dispersion of interest rates between markets, with a smaller dispersion measure corresponding to a higher degree of integration.2 This study concentrates exclusively on the covariation between equity prices as a measure of integration since aggregate information on dividend payments is not available for most countries. In an attempt to measure the extent of covariation between national stock markets and to isolate and identify the patterns of linkage Received for publication June 28, 1972. Revision accepted for publication January 12, 19,73. * The views expressed in this paper are those of the author and not necessarily those of the International Monetary Fund. 1Legal constraints on the share of a United States institution's portfolio that may be invested in foreign assets may also have influenced the repatriation of portfolio capital. 2See R. N. Cooper, Towards an International Capital Market?, Center Discussion Paper number 68, Economic Growth Center, Yale University, July 1969. The question of the integration of national stock markets is briefly raised but is not pursued because price earnings ratios are not available in many countries.